Regional Differences in Sugar-Sweetened Beverage Intake among US Adults - Park, Sohyun; McGuire, Lisa C.; Galuska, Deborah A. (Journal of the Academy of Nutrition and Dietetics, 2015)
Higher consumption of sugar-sweetened beverages (SSBs) is associated with obesity and type 2 diabetes, and the prevalence of obesity varies by geographic region. Although information on whether SSB intake differs geographically could be valuable for designing targeted interventions, this information is limited. This cross-sectional study examined associations between living in specific census regions and frequency of SSB consumption among US adults using 2010 National Health Interview Survey data (n=25,431). SSB consumption was defined as the consumption of four types of beverages (regular sugar-sweetened carbonated beverages, fruit drinks, sports/energy drinks, and sweetened coffee/tea drinks). The exposure variable was census region of residence (Northeast, Midwest, South, and West). We used multivariable logistic regression to estimate adjusted odds ratios (aORs) and 95% CIs for drinking SSBs after controlling for sociodemographic characteristics. Approximately 64% of adults consumed SSBs ≥1 time/day. The odds of drinking SSBs ≥1 time/day were significantly higher among adults living in the Northeast (aOR=1.13; 95% CI=1.01, 1.26) but lower among adults living in the Midwest (aOR=0.70; 95% CI=0.64, 0.78) or West (aOR=0.78; 95% CI=0.71, 0.87) compared with those living in the South. By type of SSB, the odds of drinking regular soda ≥1 time/day was significantly lower among adults living in the Northeast (aOR=0.51; 95% CI=0.45, 0.57), Midwest (aOR=0.86; 95% CI=0.78, 0.96), or West (aOR=0.56; 95% CI=0.51, 0.62) than those living in the South. The odds of drinking sports/energy drinks ≥1 time/day were significantly lower among adults living in the West (aOR=0.77; 95% CI=0.64, 0.93) than those living in the South. The odds of drinking a sweetened coffee/tea drink ≥1 time/day were significantly higher among adults living in the Northeast (aOR=1.60; 95% CI=1.43, 1.78) but lower among adults living in the Midwest (aOR=0.70; 95% CI=0.62, 0.78) than those living in the South. Total frequency of SSB consumption and types of SSB consumption differed by geographic region. Interventions to reduce SSB intake could consider regional variations in SSB intake, particularly when more local data are not available.